Enhancement of Wang-Yin-Wang improved least significant BIT algorithm applied in image steganography. - Harry Chris John C. Decapia, John Christopher D. Ilacad. 4 0 16; 5
ABSTRACT: In today's world image steganography, especially when utilizing ,ethods like the LSB (Least Significant Bit) methodology is crucial for secret communication. The least significant pixel values of an image can be changed using the LSB technique to encode hidden messages that are not visible to the human eye. Various industries, involving digital watermaking, secure data transmission, and privacy protection, rely on this technology. Like any other steganographic method, the LSB method poses ethical and legal concerns regarding abuse. This shows how important it is to apply and understand responsibility its use in today's technology. The goal of Wang-Yin-Wang's LSB enhancement is to make the original LSB algorithm more secure and resilient. Their tests demonstrated that the enhanced method outperforms the original LSB. To enhance the Wang-Yin-Wang algorithm and add new features, certain changes can still be performed. First, 24-bit carrier images are not supported by the algorithm. Second, if the size of the hidden image is larger than the carrier image, the method cannot keep all the hidden image's bits because there are not enough pixel values. Finally, the method does not protect the confidentiality of the content of the concealed image. With this problem, the researchers resolve these issues and enhance the algorithm's resilience, capacity, and imperceptibility. Initially, the secret message is encrypted using Advanced Rncryption Standard - 128 (AES-128) to conceal its existence in the picture before it is embedded. The Lempel-Ziv-Welch (LZW) compression method was then used by the researchers to minimize the size of the hidden image. Ultimately, the carrier image's ability to absorb bits from the hidden picture is increased by enabling RGB images using Aqeel and Racheel's LSB (3-2-3) approach. According to the results, the enhanced LSB method reduces the size of the hidden image that can be embedded with the carrier image. Additionally, the encrypted hidden image disguises its presence in the carrier image disguises its presence in the carrier image before the embedding process, and the stego-images display less visual distortion than Wang-Yin-Wang's algorithm.
Undergraduate Thesis : (Bachelor of Science in Computer Science) - Pamantasan ng Lungsod ng Maynila, 2024.
Keywords: 2 -- 0; 6; 20; 20; 2